Asuhan Keperawatan Pada Ny. R Dengan Gangguan Sistem Kardiovaskular: Congestive Heart Failure (CHF) Dengan Masalah Bersihan Jalan Napas Tidak Efektif Di Ruang Melati RSUD Banyumas - Afni Setia Dewi; Titis Wening Setyoharsih (STIKES Columbia Asia Medan, 2026)
Background: Congestive Heart Failure (CHF) is a condition characterized by the inability of the heart to pump blood optimally, resulting in the accumulation of fluid in the lungs and other organs. This condition frequently causes ineffective airway clearance due to hypersecretion of the airway. Objective: This study aims to describe the comprehensive nursing care provided to Ny. R with Cardiovascular System Disorder: Congestive Heart Failure (CHF) with the main nursing problem of ineffective airway clearance at the Melati Ward of RSUD Banyumas. Method: This study used a descriptive method through a case study approach. Data were collected through interviews, physical examination, observation, and documentation. Results: Two nursing diagnoses were identified: (1) ineffective airway clearance related to airway hypersecretion, and (2) activity intolerance related to an imbalance between oxygen supply and demand. Nursing interventions included airway management and energy management. After two days of implementation (January 27–28, 2026), the first diagnosis was resolved and the second was partially resolved, with continued interventions recommended including monitoring of physical and emotional fatigue, advising bed rest, and monitoring vital signs. Conclusion: Comprehensive nursing care with appropriate interventions can effectively address ineffective airway clearance in CHF patients.